2023
DOI: 10.1038/s41591-023-02611-1
|View full text |Cite
|
Sign up to set email alerts
|

Viral and host mediators of non-suppressible HIV-1 viremia

Abbas Mohammadi,
Behzad Etemad,
Xin Zhang
et al.

Abstract: Non-suppressible HIV-1 viremia (NSV) is defined as persistent low-level viremia on antiretroviral therapy (ART) without evidence of ART non-adherence or significant drug resistance. Unraveling the mechanisms behind NSV would broaden our understanding of HIV-1 persistence. Here we analyzed plasma virus sequences in eight ART-treated individuals with NSV (88% male) and show that they are composed of large clones without evidence of viral evolution over time in those with longitudinal samples. We defined provirus… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 94 publications
0
4
0
Order By: Relevance
“…H3K36me3 modified histones mediate HIV integration in vitro [ 53 ], and HIV integration sites in vivo are enriched in H3K36me3 abundant regions [ 54 ]. Nevertheless, our data indicate that HIV integration is independent of H3K36me3.…”
Section: Resultsmentioning
confidence: 99%
“…H3K36me3 modified histones mediate HIV integration in vitro [ 53 ], and HIV integration sites in vivo are enriched in H3K36me3 abundant regions [ 54 ]. Nevertheless, our data indicate that HIV integration is independent of H3K36me3.…”
Section: Resultsmentioning
confidence: 99%
“…Sequence analysis revealed residual plasma viremia on ART was due in each case to a single (but different) barcoded virus lineage in each of the 3 animals ( S3 Fig ). Although the current study did not include confirmatory integration site sequencing, we posit that the most plausible explanation for this residual non-suppressible viremia is that it reflects the cumulative virus production from an early established and clonally expanded infected CD4 + T cell population [ 34 , 40 ]. Interestingly, the virus in the remaining RM generated known drug resistance mutations [ 21 , 22 ] which caused a complete failure to suppress.…”
Section: Discussionmentioning
confidence: 99%
“…The chromatin landscape near the integration sites on HIV-1 latency can also play a role in restricting HIV reactivation. Studies of rare people with HIV (PWH) with nonsuppressible HIV-1 viremia (NSV) have shown that the integration sites of the intact producer provirus that are responsible for generating sequencing-matching plasma viruses in the circulation show significant enrichment of activating H3K36 methylation marks [ 34 ]. These findings align with a recent study showing that nucleosomes containing H3K36me3 are preferentially targeted by the HIV-1 preintegration complex [ 35 ].…”
Section: Epigenetic Control Of Hiv-1 Latencymentioning
confidence: 99%